Bibliometric analysis of the effects of athletes’ mental fatigue on motivation - Kaihao, Yu; Samsudin, Shamsularffin; Abd Manaf, Faizal Bin; Ramlan, Mohd Aswad; Yuxin, Cong; Liu, Dezheng (Human Resources Management Academic Research Society (HRMARS), 2024)
Mental fatigue is a psychological state caused by prolonged cognitive tasks, sustained stress, or strenuous physical activity, characterized by poor concentration, reduced decision-making ability, mood swings, and decreased motivation. In sports, athletes often face long training sessions, intensive competition schedules, and various daily stresses, which can lead to the development of mental fatigue. Mental fatigue not only affects the physical state of athletes but also has negative effects on their psychological state, weakening their motivation and enthusiasm for training and competition, thereby impacting their competitive performance and training outcomes. This paper aims to systematically review and analyze studies on the effects of mental fatigue on athletes' motivation using bibliometric analysis through CiteSpace software. The research explores the mechanisms, degree of influence, and factors affecting how mental fatigue impacts athletes' motivation. The findings indicate that mental fatigue affects athletes' brain function and psychological state, subsequently influencing their motivation levels and performance. Additionally, the impact of mental fatigue varies due to individual differences and environmental factors, such as stress in training and competition environments, daily life pressures, and the effectiveness of social support and counseling. The research objectives include analyzing annual publications in this field, identifying key disciplines and journals, uncovering influential institutions, authors, and collaborations, understanding current research hotspots, and exploring existing issues to provide scientific references for sports training and psychological interventions.